Developing a coherent monitoring system for Mediterranean grasslands - Louhaichi M.; Johnson M.D.; Clark P.E.; Belgacem Areiz O.; Johnson D. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Grasslands are one of the world‘s most widespread vegetation types, covering nearly 20% of the land surface and represent a major source of production of agricultural products. However, grassland vegetation across the Mediterranean region is changing at an unanticipated rate. These changes are the result of climatic and socio-economic changes. Because changes in agro-ecosystems affect the livelihoods and development of rural communities, it is important that planners and policy makers be able to determine grassland condition and trend in relation to climatic and managerial factors at specific locations. Over the past decade we have been developing monitoring technologies and protocols that can be used at local scales which speed the collection, processing, and storage of indicators of grassland health. By coupling digital photography, GPS technologies, information collected with accessory devices, and computer software applied in a strict monitoring protocol, we are able to rapidly monitor grassland vegetation. Repeated measurements over time at the same locations provide information regarding environmental trend and rate of change. When we couple our local scale measurements with landscape scale remote sensing data such as satellite or high altitude aerial photography, we have a more complete picture of vegetation dynamics and system change which facilitates interpretation and development of mitigation strategies.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)